Probing the effect of molecular structure and compositions in extracted oil on the characteristics of needle coke. (1st October 2021) - Zhang, Zhichen; Du, Hui; Guo, Shuhai; Lou, Bin; Yu, Ran; Gong, Xin; Li, Zhiheng; Li, Min; Duan, Yajing; Yuan, Huizhi; Liu, Dong
Graphical abstract: Highlights: We reported the effect of extraction of low temperature coal tar on needle coke. The furfural extraction enriched the composition of aromatics. The furfural extraction modified the molecular structures. Modification improved the structure of derived needle coke. Abstract: Needle coke have received much attention as a high-quality raw material for high power electrode due to its excellent electrical conductivity and low thermal expansion. In order to further investigate the effect of the molecular structure and key compositions of raw material on the quality of needle coke, a series of furfural extracts of low-temperature coal tar were adopted to prepare needle coke by a two-stage pyrolysis method. With the increase of extracted temperature and solvent to oil ratio, it was found that the alkyl side chains in the extracted oil increased, as well as the pyrenes and phenanthrenes contents. During the pyrolysis process, more and longer alkyl side chains generated more alkyl active sites for the polycondensation, which was conducive to the orientation of mesophase stacking. Nonetheless, excessive alkyl active sites would lead to the steric hindrance and structural strains. Using the extracted oil with appropriate alkyl side chains obtained under the solvent to oil ratio of 1.0 at 60 ℃, the prepared needle coke showed the maximum level of planar self-assembly and the enhanced acicular domain content of 67.36 vol%. Moreover, the Py/Ph ratio in the range of 0.76–0.93 controlled the balance of the stability and kinetics during the preparation.